2021
DOI: 10.1002/jcla.23871
|View full text |Cite
|
Sign up to set email alerts
|

Integrating serum microRNAs and electronic health records improved the diagnosis of tuberculosis

Abstract: Background To verify the differential expression of miR‐30c and miR‐142‐3p between tuberculosis patients and healthy controls and to investigate the performance of microRNA (miRNA) and subsequently models for the diagnosis of tuberculosis (TB). Methods We followed up 460 subjects suspected of TB, and finally enrolled 132 patients, including 60 TB patients, 24 non‐TB disease controls (TB‐DCs), and 48 healthy controls (HCs). The differential expression of miR‐30c and miR‐142‐3p in serum samples of the TB patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…Qi et al, reported that the combination of miR-361-5p, miR-889, and miR-576-3p displayed strong potential for diagnostic utility with a high AUC value of 0.863 [ 51 ]. Additionally, previous studies have suggested that miR-30c and miR-142-3p serve as diagnostic biomarkers, with AUC values of 0.67 and 0.75, respectively [ 52 ]. Jia-Yi Cui et al, reported that AUC values of miR-769-5p, miR-320a, and miR-22-3p range from 0.69 to 0.97 in qRT-PCR validation [ 53 ].…”
Section: Discussionmentioning
confidence: 99%
“…Qi et al, reported that the combination of miR-361-5p, miR-889, and miR-576-3p displayed strong potential for diagnostic utility with a high AUC value of 0.863 [ 51 ]. Additionally, previous studies have suggested that miR-30c and miR-142-3p serve as diagnostic biomarkers, with AUC values of 0.67 and 0.75, respectively [ 52 ]. Jia-Yi Cui et al, reported that AUC values of miR-769-5p, miR-320a, and miR-22-3p range from 0.69 to 0.97 in qRT-PCR validation [ 53 ].…”
Section: Discussionmentioning
confidence: 99%
“…These circulating plasma miRNAs can further enable the differential diagnosis of latent and active TB. Diagnostic performance of miRNA can be increased by integrating serum miRNAs with diagnostic models developed by miRNA characteristics and electronic health records (HERs) [61,62] and bioinformatics analysis [63]. Even though miRNA-based detection of TB is convenient in diagnosis in children, the method is challenging to adopt in resource-limited settings.…”
Section: Microrna Detectionmentioning
confidence: 99%
“…After obtaining this result, they utilized a combination of proteins and miRNAs to further improve the model ( 185 ). Another group combined miR-142-3p with electronic health record (EHR) data to detect TB, and the AUC reached 0.94 ( 186 ). Compared with LTBI patients, hsa-miR-1246, hsa-miR-2110, hsa-miR-370-3p, hsa-miR-193b-5p, and hsa-miR-28-3p are specifically expressed in TB cohorts ( 187 ).…”
Section: Noncoding Rnas As Biomarkers In Tuberculosismentioning
confidence: 99%